‘All the world’s a stage’ – Shakespeare in English Language Education: Topics – Tasks – Selected Texts - Schönbauer, Daniel, MEd (Tectum Verlag, 2021)
If asked about which writer they associate with Anglophone literature, most students might come up with William Shakespeare, who has also become an integral part of British cultural identity. As a matter of fact, his works keep delighting audiences worldwide. However, EFL learners might struggle with the complexity and ambiguity of his plays and poetry. This anthology provides perspectives of how to read and teach Shakespeare. Thereby, it focusses on a variety of texts worth implementing in teaching units. The articles take the perspective of literary and cultural studies as base and aim at interconnecting it to major con-cepts and theories of teaching literature and culture and provides ideas of how to actively teach Shakespeare in class.With contributions byAlina Dresen, Julia Falter, Jessie-May Franken, Sophie Gnech, Svenja Harzem, Michelle Hausschild, Christina Kattwinkel, Ruth Kühsel, Dr. Imke Lichterfeld, Milena Niesen, Rahel Ovesiek, Daniel Schönbauer, Alina Tary, Sofia Ullah, Daniel Voges und Bernadette von Tongelen.